Longstanding and Refractory Anti-Muscle Specific Tyrosine Kinase Antibody-Associated Myasthenia Gravis (Anti-MuSK-MG) in a Child Successfully Treated with Rituximab. Issue 1 (2nd January 2019) - Weger, Steven; Appendino, Juan Pablo; Clark, Ian H.
ABSTRACT: Anti-muscle specific tyrosine kinase antibody-associated myasthenia gravis (MuSK-MG) is a rare subtype of MG characterized by more frequent relapses and a clinical course that is refractory to standard treatments. Rituximab, a monoclonal antibody targeting CD20+ B cells, has been used effectively in the adult population to achieve stable remission. We describe a pediatric patient with MuSK-MG who demonstrated an excellent response to rituximab after failing standard therapy.